Three-dimensional laser combined with C-arm computed tomography-assisted puncture of intracerebral hemorrhage - Zhao, Hongwei; Zhang, Tao; Li, Min; Gao, Yang; Wang, Shuangquan; Jiang, Rongcai; Li, Zefu (Frontiers in Endocrinology, 2023)
Background Intracerebral hemorrhage (ICH) is the deadliest subtype of stroke, with a 30-day case fatality rate of approximately 40%. Timely and accurate treatment is essential to facilitate recovery. The introduction of stereotactic instruments and navigation systems has greatly improved the accuracy of surgical treatment. In this study, we explored the application and effects of a three-dimensional (3D) laser combined with C-arm computed tomography (CT) on ICH puncture. Materials and methods According to the principle of randomness, 118 patients with ICH were divided into control and experimental groups. The control group was treated with CT-guided puncture, and the experimental group was treated with 3D laser combined with C-arm CT puncture. The hematoma clearance rates at 3, 5, and 7 days after surgery and the prognosis at 1, 3, and 6 months after surgery were compared between the two groups. Results The hematoma clearance rates of the group using 3D laser combined with C-arm CT at 3, 5, and 7 days after surgery were significantly higher than those of the control group, and the difference was statistically significant (p < 0.05). One month postoperatively, the daily living ability (ADL) grading and recovery of the patients in the test group was significantly better than those of the control group (p < 0.05), but there was no statistically significant difference in ADL 3 and 6 months after surgery (p > 0.05). Conclusion 3D laser combined with C-arm CT puncture has the advantages of real-time guidance, accurate positioning, and simple operation. It is an effective minimally invasive surgical method that is easy to master.